SP0017 Lessons learned from lyme disease: only persistent bacteria or autoimmunity. (1st June 2001) - Huber, B
Abstract : Antibiotic treatment-resistant Lyme arthritis is a chronic inflammatory joint disease, associated with a limited number of MHC alleles, including HLA DRb1*0401. A marked antibody and T cell response to outer surface protein A (OspA) of Borrelia burgdorferi, the causative agent of Lyme disease, is often seen during prolonged episodes of arthritis. An autoimmune mechanism has been implicated due to the lack of the Borrelia burgdorferi antigen in the target organ and apparent cross-reaction at the T cell level between the bacterial OspA and a self-protein, LFA-1aL. To directly test this hypothesis, we isolated and cloned T cells specific for the immunodominant epitope of OspA, OspA165–174, from five DRb1*0401+ patients, using OspA-class II tetramers. These clones were tested for their ability to respond to peptide containing the human homologue of OspA165–174, LFA-1aL332–340, as determined by proliferation and cytokine production. All of the T cell lines responded to minute concentrations of OspA165–174 by proliferation and secretion o IFN-g and IL-13. In contrast, larger concentrations of LFA-1aL326–345 were required for stimulation, and only 10% of the clones proliferated vigorously. With this stimulation, approximately half of the cell lines secreted IL-13 but produced no IFN-g. LFA-1aL-tetramers required a 2.5- to 25-fold higher concentration to stain dual reactive clones than OspA tetramer. Our analysis at the clonal level demonstrate that LFA-1aL326–345 behaves as an analogue for the OspA peptide, but a greater concentration of the LFA-1 peptide is required and an altered cytokine response is elicited. Thus, a single bacterial-specific T cell may respond to a cross-reactive human protein, LFA-1aL, indicating a role for molecular mimicry, and thus, autoimmunity, in treatment resistant Lyme arthritis.